Can daily actigraphic profiles distinguish between different mood states in inpatients with bipolar disorder? An observational study - Zhang, Yinlin; Deng, Xinyi; Wang, Xueqian; Luo, Huirong; Lei, Xu; Luo, Qinghua (Frontiers in Psychiatry, 2023)
Background: Criterion A changes for bipolar disorder (BD) in the Diagnostic and Statistical Manual of Mental Disorders–Fifth Edition yield new difficulties in diagnosis. Actigraphy has been used to capture the activity features of patients with BD. However, it remains unclear whether long-term actigraphic data could distinguish between different mood states in hospitalized patients with BD. Methods: In this observational study, 30 hospitalized patients with BD were included. Wrist-worn actigraphs were used to monitor motor activity. The patients were divided into bipolar disorder–depression (BD-D), bipolar disorder–mania (BD-M), and bipolar disorder–mixed state (BD-MS) groups. Motor activity differences were estimated using non-parametric analyses between and within the three groups. Results: The mean 24-hour activity level differed between the groups. In the between-group analysis, the intra-individual fluctuation and minute-to-minute variability in the morning and the mean activity level and minute-to-minute variability in the evening significantly differed between the BD-M and BD-MS groups. In the within-group analysis, the BD-M group showed a disrupted circadian rhythm and reduced activity complexity at night. Both the BD-D and BD-MS groups demonstrated significant differences between several parameters obtained in the morning and evening. Conclusions: The mean activity levels during the relatively long monitoring period and the intra-day variation within the groups could reflect the differences in motor activity. Sustained activity monitoring may clarify the emotional states and provide information for clinical diagnosis.